2022
DOI: 10.1002/er.7990
|View full text |Cite
|
Sign up to set email alerts
|

Liquid cooling system optimization for a cell‐to‐pack battery module under fast charging

Abstract: Summary Cell‐to‐pack (CTP) structure has been proposed for electric vehicles (EVs). However, massive heat will be generated under fast charging. To address the temperature control and thermal uniformity issues of CTP module under fast charging, experiments and computational fluid dynamics (CFD) analysis are carried out for a bottom liquid cooling plate based–CTP battery module. The impact of the channel height, channel width, coolant flow rate, and coolant temperature on the temperature and temperature differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[160][161][162] As the field advances, the focus is increasingly shifting toward enhancing the efficiency and effectiveness of these liquid cooling systems. [43,163] This enhancement involves several vital strategies. First, there is a drive to optimize the design of cooling channels, which significantly impacts the system's thermal performance.…”
Section: Advanced Liquid Cooling Systemsmentioning
confidence: 99%
“…[160][161][162] As the field advances, the focus is increasingly shifting toward enhancing the efficiency and effectiveness of these liquid cooling systems. [43,163] This enhancement involves several vital strategies. First, there is a drive to optimize the design of cooling channels, which significantly impacts the system's thermal performance.…”
Section: Advanced Liquid Cooling Systemsmentioning
confidence: 99%
“…114 created a monitoring system to prevent lithium plating in parallel-connected battery modules when charging them, which decreased the likelihood of lithium plating when the battery is being charged and shortened the total charging time by 18%, in addition to reducing the peak battery temperature by about 9.8% in comparison to the traditional CC–CV charging technique. Sun et al 115 investigated the temperature and inhomogeneous heat problem of the battery system module under rapid charging circumstances and a computational fluid dynamics (CFD) study was conducted to examine how the temperature of the battery system module was affected by the following variables: channel width, coolant flow rate, and coolant temperature, and it was verified by simulation and experiment that the temperature of the battery was positively affected by both the flow rate and temperature, leading to a maximum temperature reduction of 10.93% and 15.12%, respectively. Chen et al 116 proposed that the battery system module can be safely and quickly charged in fast-charging environments, where the spacing between the battery cells, the transverse and longitudinal width of the channel, and the NSGA II genetic algorithm were used to do a multi-objective optimization, while considering the channel depth and other parameters, which yielded that the depth of the channel had the greatest influence.…”
Section: Power Battery Module Charging Strategymentioning
confidence: 99%
“…The simulation results showed that under extreme conditions (4C charging), the maximum temperature of the battery reached 79 • C, implying that the cold plate was not able to meet the heat dissipation needs of the system, and the battery might experience thermal runaway. In order to solve the heat dissipation problem in the CTP battery system, Sun et al [110] optimized the structure of indirect liquid cooling under fast charging to study the effects of channel height, channel width, coolant flow, and coolant temperature on the battery temperature. The simulation results found that the coolant flow rate and temperature are the main factors affecting the battery temperature, while the channel height and width have little influence, and the temperature of the battery pack can be controlled at 30-35 • C under an effective configuration.…”
Section: Structure Optimization Of Liquid Cooling Systemmentioning
confidence: 99%